1998
DOI: 10.1080/j.1600-0412.1998.770204.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of human placental lactogen, pregnancy-associated plasma protein A and endometrial secretory protein PP14 in first trimester of diabetic pregnancy

Abstract: In first trimester of diabetic pregnancy there appears to be both a more general depression of trophoblast function, and also a specific depression of the hPL release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This study has shown that in pregnancies with maternal IDDM, fetal NT thickness and maternal serum free β-hCG and PAPP-A are not significantly different from normal. In contrast, two previous studies including 34 and 79 diabetic pregnancies have reported that the levels of PAPP-A may be reduced by as much as 20% (Pedersen et al, 1998;Ong et al, 2000) and the levels of free β-hCG may be reduced by 25% (Ong et al, 2000). In the combined data from this and the previous studies, the median MoM for free β-hCG in 114 cases was 0.82, some 18% lower than in an unaffected population and the median MoM for PAPP-A in 193 cases was 0.89, some 11% lower than in an unaffected population.…”
Section: Discussionmentioning
confidence: 57%
“…This study has shown that in pregnancies with maternal IDDM, fetal NT thickness and maternal serum free β-hCG and PAPP-A are not significantly different from normal. In contrast, two previous studies including 34 and 79 diabetic pregnancies have reported that the levels of PAPP-A may be reduced by as much as 20% (Pedersen et al, 1998;Ong et al, 2000) and the levels of free β-hCG may be reduced by 25% (Ong et al, 2000). In the combined data from this and the previous studies, the median MoM for free β-hCG in 114 cases was 0.82, some 18% lower than in an unaffected population and the median MoM for PAPP-A in 193 cases was 0.89, some 11% lower than in an unaffected population.…”
Section: Discussionmentioning
confidence: 57%
“…Also, in the multivariate model, feto-placental markers did not prove to be significant in detecting women at risk for GDM. Low fβhCG and PAPP-A levels at 10 to 14 gestational weeks in women with pre-existing diabetes mellitus and with GDM were noted by Ong et al, 2000, and low PAPP-A levels in pre-existing diabetes mellitus were noted by Pedersen et al, 1998. In the second trimester, AFP, uE3 and hCG were reduced in women with insulin-dependent diabetes; for the purpose of screening for T21, the corrections for some markers are necessary (Wald et al, 1992), although some have argued that the improved quality of diabetic care renders correction now inappropriate. In our study, only one woman with pre-existing diabetes mellitus was included; her markers were low, and she delivered an LGA baby.…”
Section: Discussionmentioning
confidence: 96%
“…Unfortunately, the number of included women was small and further studies are needed to confirm this hypothesis. In two other studies, low PAPP-A levels in diabetic pregnancies were reported (Ong et al, 2000;Pedersen et al, 1998), yet the data on the birth of LGA babies is missing. In women with GDM, and probably also in those with pre-existing diabetes, PAPP-A levels do not seem to be useful in predicting LGA babies because of decreased PAPP-A levels in GDM women.…”
Section: Discussionmentioning
confidence: 99%
“…In five previous studies examining preexisting diabetes, but not subdivided according to type, serum PAPP-A was reduced by 5–20% [14,15,16,17,18] and such variation may be the consequence of the proportion of the types of diabetes in the different study populations. The prevalence of diabetes is low, and therefore, adjustments in serum biochemistry would not influence the overall performance of first trimester-combined screening for aneuploidies.…”
Section: Discussionmentioning
confidence: 99%